Resources Scheduling Algorithm in Power Wireless Private Network Based on SDON - Ningzhe Xing (International Journal of Optics)
With the increasing of the business carried by the power wireless private network and the continuous development of the new network technology, the problems in the traditional mode of power wireless private network are becoming more and more obvious. In order to solve the problems such as poor business service quality, low system throughput, and fairness problems in the uplink resource scheduling process of power wireless private network, a dynamic uplink resource scheduling algorithm is proposed on the basis of Software Defined Optical Network (SDON). By studying the business characteristics of the uplink transmission of power wireless network, the priority of the service is evaluated before the resource scheduling is carried out. According to the characteristics of OFDM resource allocation and the numerical control separation and programmable feature of SDON, different scheduling methods are designed for different services. Simulation analysis shows that this algorithm can effectively improve the system throughput, guarantee QoS, and improve the transmission performance of different services.